2007
DOI: 10.1556/avet.55.2007.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Study on the species-specificity of Isospora michaelbakeri by experimental infection

Abstract: Isospora michaelbakeri is one of the Isospora species most commonly found in the wild field, which can cause severe infection and mortality in young sparrows. In this study, we selected I. michaelbakeri (Chung Hsing strain) as a pathogen to orally inoculate russet sparrows (Passer rutilans), spotted munia (Lonchura punctulata), canary (Serinus canaria), Java sparrows (Padda oryzivora), chicken (Gallus domesticus), ducks (Anas platyrhynchos) and BALB/c mice. The results indicated that I. michaelbakeri infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In these experiments, oöcysts of I. michaelbakeri Grulet, Landau & Baccam, 1982, a parasite of the sparrow Passer rutilans (Temminck), were used to inoculate their natural host and the following birds: the estrildids passerines Lonchura punctulata (L.) and Padda oryzivora (L.); the fringillid passerine Serinus canaria; the galliform Gallus gallus (L.); and the anseriform Anas platyrhynchos (L.). In support of the genus-specific concept, only the sparrow P. rutilans developed an infection (Tung et al, 2007).…”
Section: Host-specificitymentioning
confidence: 74%
See 1 more Smart Citation
“…In these experiments, oöcysts of I. michaelbakeri Grulet, Landau & Baccam, 1982, a parasite of the sparrow Passer rutilans (Temminck), were used to inoculate their natural host and the following birds: the estrildids passerines Lonchura punctulata (L.) and Padda oryzivora (L.); the fringillid passerine Serinus canaria; the galliform Gallus gallus (L.); and the anseriform Anas platyrhynchos (L.). In support of the genus-specific concept, only the sparrow P. rutilans developed an infection (Tung et al, 2007).…”
Section: Host-specificitymentioning
confidence: 74%
“…These authors put forward the concept of intra-familial specificity when they suggested that a new coccidian species should be compared in detail with the coccidian species that is most structurally similar to it within the same host family. However, Tung et al (2007) considered that this concept should be genus-specific based on data from studies of experimental infection. In these experiments, oöcysts of I. michaelbakeri Grulet, Landau & Baccam, 1982, a parasite of the sparrow Passer rutilans (Temminck), were used to inoculate their natural host and the following birds: the estrildids passerines Lonchura punctulata (L.) and Padda oryzivora (L.); the fringillid passerine Serinus canaria; the galliform Gallus gallus (L.); and the anseriform Anas platyrhynchos (L.).…”
Section: Host-specificitymentioning
confidence: 99%
“…It has been experimentally documented that it represents an adaptive trait against desiccation and ultraviolet radiation (Martinaud et al 2009). Little information exists about the pathology caused by Isospora species in birds, despite significant impact of parasites on bird's fitness and reproductive success (Grulet et al 1986b;McGraw et al 2002;Hõrak et al 2004;Tung et al 2007). Avian Isospora prevalence surveys that do not take into account the diurnal periodicity of the oocyst shedding will lead to incorrect results (Filipiak et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A study of 12 species of Isospora found in sparrow showed that these species are considered highly specific because transmission of infection could not be repeated in several captive species . Another study of Isospora michaelbakeri from russet sparrows ( Passer rutilans ) showed that this species failed to infect spotted munias ( Lonchura punctulate ), canaries ( Serinus canaria ), Java sparrows ( Padda oryzivora ), chickens ( Gallus domesticus ) or ducks ( Anas platyrhynchos ) . Prevalence studies and case studies indicate that Isospora has a worldwide distribution, with a high prevalence (up to 90%) reported in greenfinches in Estonia, blackbirds ( Turdus merula ) in Germany, sparrows in Israel and a range of passerines in New Zealand …”
Section: Methodsmentioning
confidence: 99%